Relationship between natural environment theme picture book design and children’s cognitive development: a systematic review - Chao Sun; Norhuzailin Hussain; Azmiah Abd Ghafar (Cogent Arts & Humanities)
As a primary educational tool for early cognitive and emotional development, picture books are essential for children to learn about and understand the world. Natural environment theme picture books allow children to connect with nature, fostering environmental awareness and conservation values. These books’ visual appeal and integrated design directly influence children’s interest and engagement, underscoring the importance of well-considered picture book design. This study systematically reviewed 32 articles from 2000 to 2022, including Chinese literature, to analyse research trends and gaps in the relationship between picture book design and cognitive development. This study found that most of the recent research is based on the concept of mental development and the cognitive theory of picture books and often supports the research together with theories or concepts of education, design, and environment and mainly adopts the methods of case study, content analysis, and observation. Most of the research focuses on the combined design elements of the picture book, especially the images and the text-image relationship. However, significant gaps remain in exploring the interdisciplinary and multi-method approaches needed to fully understand the impact of picture book design on cognitive development.